Identification and Phylogenetic Analysis of Basic Helix-Loop-Helix Genes in the Diamondback Moth. Issue 3 (12th June 2018) - Zeng, Zhen; Wang, Yong; Johnson, Nana Adwoa Nkuma; Wang, Guang-Dong; Yao, Qin; Chen, Ke-Ping
Abstract: Basic helix-loop-helix (bHLH) transcription factors play essential roles in regulating eukaryotic developmental and physiological processes such as neuron generation, myocyte formation, intestinal tissue development, and response to environmental stress. In this study, the diamondback moth, Plutella xylostella (L.) (Lepidoptera: Plutellidae), genome was found to encode 52 bHLH genes. All 52 P. xylostella bHLH ( PxbHLH ) genes were classified into correspondent bHLH families according to their orthology with bHLHs from fruit fly and other insect species. Among these 52 PxbHLH genes, 19 have been annotated consistently with our classification in GenBank database. The remaining 33 PxbHLH genes are either annotated as general bHLH genes or as hypothetical genes. Therefore, our data provide useful information for updating annotations to PxbHLH genes. P. xylostella has four stem cell leukemia ( SCL ) genes (one of them has three copies), two Dys genes, two copies of MyoR, Mitf, and Sima genes, and three copies of Sage genes. Further studies may be conducted to elucidate functions of these specific bHLH genes in regulating P. xylostella growth and development.